CONSTITUTIONAL ASPECTS OF CHANGING THE PRESIDENT'S TERM OF OFFICE TO 3 (THREE) PERIOD FROM THE PERSPECTIVE OF INDONESIAN CONSTITUTIONAL LAW - Situmorang, Andri Candro (Proceeding International Conference of Science Technology and Social Humanities, 2022)
The large role of the president, especially for a country that adheres to a presidential system of government, has had consequences for the sustainability of democracy. Indonesia is a country that adheres to a presidential system, as confirmed in Article 4 paragraph (1) of the 1945 Constitution which states that "The President of the Republic of Indonesia holds governmental powers according to the Constitution". Apart from this, the president's powers are also regulated in Chapter III of the 1945 Constitution concerning the Powers of State Government, containing 17 articles which regulate various aspects regarding the president and the presidential institution. This shows that the portion of the President's power is so large that it is natural that the topic of the presidency is always interesting to discuss. The problem formulation that will be the main topic of discussion is; What are the problems with regulating the presidential term of office in Indonesia? How is the presidential term changed to 3 (three) terms through amendments to the 1945 Constitution from the perspective of Indonesian Constitutional Law? This research uses descriptive research, with a qualitative research type, and uses a normative juridical research type, and this research uses library data collection methods (library research). In writing this thesis, the author believes that the regulation of the President's term of office is regulated in Article 7 of the 1945 Constitution. Since the era of President SBY to Jokowi, the discourse of increasing the presidential term of office has always been raised.